Balancing Innovation and Sustainability: Learn the Potential Impact on the Environment of Bitcoin Mining - Hossain, Mohammad Ikbal; Hussain, Muhammad Imam; Arobee, Ayesha; Zim, Md Nasim Fardous; Badhon, Md Bahauddin; Akter, Shahanaz (Journal of Knowledge Management Practice, 2025)
Convergence of technological development and sustainable development principles in the context of Bitcoin mining, are the cross-cutting issues this study is poised to address. Given the increased usage of Bitcoin, there have been increasing environmental concerns about electricity consumption and the carbon footprint of the mining processes. The study emphasizes the primary Bitcoin mining steps about how the process becomes energy-ravenous due to the proof-of-work mechanism attached to it. It also evaluates the potential environmental impact arising from mining activities with a primary focus on emissions and e-waste. Economic models demonstrate that the energy level that is used in Bitcoin mining is equivalent to the energy used by some countries, thus raising the need for appropriate management as such levels of energy use might be unsustainable. This paper also aims to predict modifiable changes in reducing potential environmental problems related to bitcoin mining by supplying some energy conservatism alternatives: energy-efficient mining equipment along with the utilization of solar energy, wind energy and water energy. Moreover, the report presents the current activities and their successes in encouraging sustainability practices in capital consumption or minimization of waste materials, policies for carbon neutrality and a framework for efficient e-waste management. There are legislative, institutional and other control measures along with incentives. They are aimed at reducing the environmental degradation caused by Bitcoin mining. The paper argues that it is possible to develop policies or employ technical solutions that would mitigate the environmental consequences of bitcoin mining without compromising the technological advancement of bitcoin mining.
Keywords: knowledge management; Bitcoin mining; environmental impact; energy consumption; sustainability; carbon footprint; renewable energy integration